A Qualitative Study to Explore and Share Successful CSR Practices related to Human and Social Capital in the Supply Chain of Companies in Indonesia - A Management Perspective - Khoo, Bee Sean (2005)
Society’s expectations of companies1 are multiple; companies are expected to deliver against committed financial targets to shareholders and are also required to be socially responsible. In this world of intense competition we have seen creation of business tools and business philosophies (Svensson 2004) (supply chain management (SCM), just in time, quick response, efficient consumer response) to remain competitive and ensure survival. The current business literature emphasises value creation; the area of knowledge covered under value chain management (VCM) and moving in the direction of value web management (VWM). The trend is moving from cost reduction to greater value creation through increasing connectivity via process, and technical integration, supported by information technology. This evolution is now achievable and driven by drivers of globalization which is declining trade and investment barriers and technological changes in communication, information and transportation (Hill 2003). This was demonstrated by Michael Dell when he introduces a new business model of personal computer purchases. Dell created a new business through shift in the mindset and behavioural change from traditional “middle men” to Dell’s direct model (Dell and Fredman 1999).